POLA ADAPTASI MASYARAKAT PESISIR GENUK KOTA SEMARANG (Patterns of Community Adaptation to Environmental Degradation in Genuk Coastal Area, Semarang) - S Sariffuddin; Arwan Putra Wijaya (Diponegoro University, 2014)
Globalization brings many consequences for Indonesian urban development and the communities. Industrialization is one of them. Globalization also brings policy transformation affecting the community’s welfare and lifestyle. One of the indicators is that local values have started to fade. The similar condition also occurs in fishermen’s and fish farmers’ settlements in Semarang, which have transformed into industrial settlements in 1980s during the industrialization period. Land conversion occurred in a short time from ponds and rice fields into factories, warehouses, and new labor’s settlements. It did not take a long time for the community’s local values to transform into the new ones influenced by the welfare level of the new community. Based on the phenomena, this study aims to understand the lifestyle of the community and its influence in managing the housing environment with Genuk coastal area of Semarang City as a case. This research has three objectives: to understand the motivation to urbanization, to comprehend the neighborhoods’ conditions, and to comprehend the influence of community’s lifestyle towards the settlement condition. In achieving the objectives, the qualitative approach supported by some quantitative data is used. The results show that there are three classes of the community influencing the environmental management. It is found that the people’s migration reasons had a big influence for the environmental management. In this case, the middle-class community is a key stakeholder to overcome the environmental problems. It becomes good initiator. On the contrary, the lower class has a less role in dealing with the environmental problems. It has even a big contribution on environmental degradation. Meanwhile, the upper class pays less attention to the environment. Only a little part of it, especially the local one, is willing to take part in the environmental management. The middle-class people consider that the problems arise due to the inappropriate planning. Unfortunately, they are not capable of dealing with the problems. On the contrary, the upper-class people consider that the issues arise from the lower class behavior that does not pay attention to the environment. As a consequence, the upper-class community is not willing to address the problems.